TAX POTENTIAL AS AN INDICATOR OF SUSTAINABLE DEVELOPMENT OF THE REGION - Yuldasheva Umida Asanaliyevna (European Science Publishing, 2023)
The tax potential is the most important indicator of the socio-economic situation of the country and a particular region, which justifies the orientation of modern state policy on its development. The article discusses various approaches to the analysis of the factors of formation and development of the tax potential of the region, which made it possible to systematize them from the point of view of the basic basis for the formation of tax potential and the mechanism of its implementation.
Keywords: tax potential, socio-economic development, factors, tax administration, direct taxes, indirect taxes, tax efficiency, optimization of the tax burden.